2015
DOI: 10.1890/15-0188.1
|View full text |Cite
|
Sign up to set email alerts
|

Soil nitrogen affects phosphorus recycling: foliar resorption and plant–soil feedbacks in a northern hardwood forest

Abstract: Previous studies have attempted to link foliar resorption of nitrogen and phosphorus to their. respective availabilities in soil, with mixed results. Based on resource optimization theory, we hypothesized that the foliar resorption of one element could be driven by the availability of another element. We tested various measures of soil N and P as predictors of N and P resorption in six tree species in 18 plots across six stands at the Bartlett Experimental Forest, New Hampshire, USA. Phosphorus resorption effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
64
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 100 publications
(78 citation statements)
references
References 59 publications
11
64
0
3
Order By: Relevance
“…Increased RBAI in response to N addition were consistent with pre‐treatment observations of high N resorption by white birch foliage in young stands (See et al. ). Thus, white birch appeared to be limited primarily by N at age 20–25 yr and by P at age 30–40 yr, suggesting the possibility of a shift in nutrient limitation early in succession, which provides tentative support for predictions of the MEL model of N limitation in early stages of recovery post‐harvest (Rastetter et al.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Increased RBAI in response to N addition were consistent with pre‐treatment observations of high N resorption by white birch foliage in young stands (See et al. ). Thus, white birch appeared to be limited primarily by N at age 20–25 yr and by P at age 30–40 yr, suggesting the possibility of a shift in nutrient limitation early in succession, which provides tentative support for predictions of the MEL model of N limitation in early stages of recovery post‐harvest (Rastetter et al.…”
Section: Discussionsupporting
confidence: 87%
“…While it may be surprising that a species with conservative traits such as beech showed the strongest response to P addition in mature forests, this pattern is consistent with pre‐treatment observations of greater P conservation by beech via foliar resorption compared to other species in mature stands (See et al. ).…”
Section: Discussionsupporting
confidence: 78%
“…, See et al. ), and thus the onset of P limitation may be delayed in forests where most of the P demand is met by this recycling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Some data showed that increased N inputs led to increases in both foliar N and P39, and the increasing uptake of N encouraged the absorption and utilization of soil P, resulting in a loss of soil P114041. Moreover, enriched soil N availability generally reduces plant N resorption while P resorption could be less affected (or even promoted)3942, leading to more N relative to P being returned to the soil through plant litter production. Meanwhile, plant litter P was difficult to breakdown because it existed in the form of phospholipid and phytate which must be processes by specialized enzymes and are affected by multiple factors43.…”
Section: Discussionmentioning
confidence: 99%